Pengembangan Instrumen Penilaian Menggunakan Aplikasi Quizizz Pada Mata Pelajaran Biologi Materi Sistem Pencernaan - Lestari, Nining Tri; Ulfa, Syarifah Widya (Jurnal Paedagogy, 2022)
This study aims to analyze the level of practicality, validity, and effectiveness of the Quizizz application as an assessment instrument for the digestive system material at SMA Negeri Panai Hulu. The research method used in this study was Research and Development (R&D) method by adopting the Borg and Gall model. Then, it is developed into eight stages of procedures: Research and Data Collection, Planning, Initial product development, Initial trial, Product revision, Field trial, Product revision final and Dissemination and implementation. This research used questionnaires, tests and interviews to collect the data. The test result data were analyzed using the gain score (N-Gain) calculation. The findings proved that the average comfort level for Biology lecturers was 87,50%, Biology teachers were 90,63%, and students were 95,7% (efficient). The average validity by material experts was 97,73% (high valid), media experts were 90,63% (very valid), and the N-Gain value was 0.78 (high effectiveness). The data indicates that the assessment instrument on the digestive system material using the Quizizz application is validated, practical, and effective.